Enhancement of Photocatalytic Activity in BiFeO3 Nanoparticles through Electrical Polarization - Jhen‐Yang Wu; Xinyu Jin; Junan Wang; Zhitao Hu; Chun‐Yi Chen; Tomoyuki Kurioka; Justin Llandro; Andrew H. Gibbons; Masato Sone; Yung‐Jung Hsu; Satoshi Okamoto; Tso‐Fu Mark Chang (Advanced Energy & Sustainability Research)
This study investigates the enhancement of photocatalytic properties in BiFeO3 nanoparticles through an additional electrical polarization (poling) pretreatment process. BiFeO3, a promising multiferroic material with a narrow bandgap of ≈2. 12 eV, is well‐suited forvisible light‐driven photocatalysis. However, its photocatalytic efficiency isoften limited by insufficient photogenerated charge availability. To address this, a poling process was employed to align the ferroelectric domains within BiFeO3 nanoparticles, improving charge separation and enhancing photocatalytic activity. The findings reveal that the poling process preserves the intrinsic bandgap of BiFeO3, maintaining its visible light absorption capability. Steady‐state photoluminescence spectroscopy shows a marked increase in the intensity in poling‐treated samples, indicating enhanced charge carrier generation. Photo degradation experiments using Indigo dye as a model pollutant demonstrate that poling‐treated BiFeO3 achieves a remarkable photodegradation efficiency of 99%, compared to 56% for untreated BiFeO3. Additionally, the poling‐treated BiFeO3 retains 65% of its initial efficiency after four cycles, highlighting its durability for sustained environmental applications. This study underscores the effectiveness of poling in enhancing the photocatalytic performance of BiFeO3 nanoparticles, providing valuable insights into the development of efficient photocatalysts via domain engineering for environmental purification technologies.